2020
DOI: 10.1101/2020.07.30.20164608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing and Assessing US County-Level COVID19 Vulnerability

Abstract: Objective: Like most of the world, the United States public health and economy are impacted by the COVID19 pandemic. However, discrete pandemic effects may not be fully realized on the macro-scale. With this perspective, our goal is to visualize spread of the pandemic and measure county-level features which may portend vulnerability. Materials and Methods: We accessed the New York Times GitHub repository COVID19 data and 2018 US Census data for all US Counties. The disparate datasets were merged and filtere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The spread of COVID-19 at the county level for the U.S. was also studied by assessing the counties’ vulnerability [11,12] or by assessing the effect of countylevel features [13,14,15]. Statistical analysis was the popular approach [13,15,11]; however, some studies used a machine learning approach [14,12]. Counties with a larger percentage of racial and ethnic minorities were affected the most [14,15,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread of COVID-19 at the county level for the U.S. was also studied by assessing the counties’ vulnerability [11,12] or by assessing the effect of countylevel features [13,14,15]. Statistical analysis was the popular approach [13,15,11]; however, some studies used a machine learning approach [14,12]. Counties with a larger percentage of racial and ethnic minorities were affected the most [14,15,13].…”
Section: Introductionmentioning
confidence: 99%
“…Millett et al [13] found that counties who had a large percentage (greater than 13 percent) of African Americans accounted for more than half of the cases and deaths nationally. Cahill et al [11] found that counties with a lower Case Fatality Rate (CFR) had a greater proportion of the population reporting having two or more races. However, no significant differences were found between High and Low CFR counties with respect to mean income or poverty rate.…”
Section: Introductionmentioning
confidence: 99%